Aliens as Immigrants: Reimagining Xenophobia in Neill Blomkamp's District 9 - Kirsten, Ashton Lauren (WritingThreeSixty: Journal or Research and Creative Text, 2019)
Neill Blomkamp's 2009 AfroSciFi film, District 9, is set in a dystopian version of Johannesburg, South Africa. The film chronicles the landing of an alien race, and these aliens are derogatorily referred to as "Prawns" and are treated as second-class citizens within their new locale. The residence (and marginalisation) of the Prawns in a squatter camp known as "District 9" sparks public outrage and goes so far as to cause riots in the city centre. I aim to analyse District 9 in terms of our socio-political climate with regards to the rise and prevalence of xenophobia and xenophobia-related protests and attacks. Xenophobia is a recurring trauma that unfolds on South African soil, largely because residents believe that foreigners present a threat to their employment opportunities and their livelihood. Foreigners are victims to the deprecatory slur of being "alien", id est. being from somewhere else. In District 9, the Prawns serve as a metaphor for immigrants that have been given refuge in our country, only for them later to be disrespected and rejected by the general public for supposedly socioeconomic reasons. The film highlights current socio-political events under the guise of science fiction, thereby causing South Africans to potentially consider their own treatment of "aliens". Blomkamp's film serves to challenge African notions of the "alien" and question the xenophobic violence present in the "Rainbow Nation". This narrative influences the positioning of Africa in a speculative future as it makes the vision of a dystopian future tangible.